Psychology : - Passer, Michael W. (McGraw-Hill, 2004)
Psychology: The Science of Mind and Behavior imparts students with a scientific understanding of the field of psychology while showing them the impact on their day-to-day existence. A simple conceptual framework within the text emphasizes relations between biological, psychological, and environmental levels of analysis and portrays the focus of modern psychology. Together with Research Close-Ups in each chapter and Beneath the Surface discussions and What Do You Think? questions, the text challenges students to think critically about psychology as a science and its impact on their lives.